Pengaruh Stres Kerja dan Lingkungan Kerja terhadap Kinerja Karyawan dengan Kepuasan Kerja sebagai Variabel Mediasi - Tri Maryati; Retria Julia Nandary (JURNAL EKONOMI BISNIS DAN MANAJEMEN, 2026)
This study aims to analyze the effect of work stress and work environment on employee performance with job satisfaction as a mediating variable at PT X. This study uses a quantitative approach with a census method of 198 employees at PT X. Data were collected through an online questionnaire (Google Form) and analyzed using Structural Equation Modeling based on Partial Least Square (SEM-PLS) with the help of SmartPLS 4.0. Based on the results of the analysis that has been done, it was found that work stress has a negative and significant effect on employee performance. Meanwhile, the work environment has a positive and significant effect on employee performance. In addition, work stress has a negative and significant effect on job satisfaction. Then, the work environment has a positive and significant effect on job satisfaction, while job satisfaction has a significant effect on employee performance. In addition, job satisfaction is able to mediate the effect of work stress and work environment on employee performance. This study provides a theoretical contribution to strengthen the understanding of the role of job satisfaction as an important mechanism that connects work stress and work environment with employee performance. Management needs to manage work stress through a balanced workload and system arrangement and create a safe and comfortable work environment to improve employee satisfaction and performance. These findings underscore the importance of job satisfaction as a basis for formulating human resource policies. This study is limited by the number of respondents, which is not fully representative of the entire population due to difficulties in communicating with employees. Furthermore, limited access to the research location, which is located outside of Yogyakarta, resulted in the distribution and collection of questionnaires being conducted only through long-distance communication. Future researchers are advised to add other variables and use research subjects from different industrial sectors to obtain a more comprehensive and comparable understanding.